Hubungan Usia, Kadar Hemoglobin Pretransfusi dan Lama Sakit terhadap Kualitas Hidup Anak Talasemia di Samarinda : Relationship of Age, Pretransfusion Hemoglobin Levels and Length of Sickness on Quality of Life in Children with Thalassemia in Samarinda - Hurria Maulana Ali; Annisa Muhyi; Yudanti Riastiti (Jurnal Sains dan Kesehatan, 2021)
The Relation between Age, Pre-transfusion Hemoglobin Level and Duration of Sickness on Quality of Life in Children with Thalassemia in Samarinda. Thalassemia is a genetic disease caused bya disturbance in the process of forming the hemoglobin chain of red blood cells that decreased the production or formation of hemoglobin. Children with Thalassemia will have transfusions for their whole life to maintain blood hemoglobin levels. The older age of the child will also increase the frequent of blood transfusions to support the child’s growth. Long and continuous transfusions also inadequate treatment will cause complications that affect the quality of life for people with Thalassemia. This study aims to analyze the relation between age, pre-transfusion hemoglobin level and duration of sickness on quality of life in children with Thalassemia in Samarinda. This research was an analytic observational study with a cross sectional design. The subjects were 32 children, aged 2-18 years, with major Thalassemia who werethe members of POPTI Samarinda. The data collected by medical records and the result from patient’s interview using PedsQl 4.0. Statistical analysis use Pearson Test. The resultshows there isno relation between age and quality of life in children with Thalassemia (p = 0.136), there is relation between pre-transfusion hemoglobin level with the quality of life in children with Thalassemia (p = 0.040) and there is relation between duration of sickness and quality of life in children with Thalassemia (p = 0.036). Based on the results of this study, it can be concluded that age has no relation to quality of life in children with Thalassemia. Pre-transfusion hemoglobin level and duration of sickness have relation to quality of life in children with Thalassemia. Keywords: Thalassemia, quality of life, age, pre-transfusion hemoglobin level, duration of sickness.